Hydrologic and edaphic constraints on Schoenoplectus acutus, Schoenoplectus californicus, and Typha latifolia in tidal marsh restoration. Issue 4 (24th April 2015) - Sloey, Taylor M.; Willis, Jonathan M.; Hester, Mark W.
<x xml:space="preserve">Abstract</x> The demand for an improved knowledge base for planning and management of tidal marsh restoration worldwide has become more fully recognized. In the Sacramento‐San Joaquin Bay Delta, California, U.S.A., concerns have arisen about the degradation of the Delta and key ecosystem services. One restoration method proposed includes intentionally breaching levees that protect agricultural lands to re‐establish a hydrology that encourages tidal marsh development. Our research investigated relevant constraints on vegetation establishment and expansion of key tidal marsh species. We transplanted three macrophyte species (Schoenoplectus acutus, Schoenoplectus californicus, and Typha latifolia) using two transplant types (rhizomes and adults) in locations that varied in hydrologic and edaphic conditions at Liberty Island, a post‐levee breach tidal marsh restoration site. Two years of monitoring revealed that transplanted adults outperformed rhizomes. In addition, S. californicus exhibited greater survival and vegetation expansion. S. californicus vegetation expansion covered a maximum area of approximately 23 m2, which is two orders of magnitude (OOM) greater than the maximum area covered by S. acutus (approximately 0.108 m2) and three OOM greater than T. latifolia (approximately 0.035 m2). Results suggest that hydrologic regime and degree of soil compaction are influential in controlling vegetation establishment and expansion. Greater vegetation expansion occurred in transplant sites characterized by a deeper surface layer of non‐compacted soil in conjunction with shorter durations of flooding. Information derived from this study is valuable to restoration planning in the Delta and other tidal marshes worldwide where these species occur, especially in terms of setting restoration goals and trajectories based on site‐specific environmental characteristics.